2019
DOI: 10.1042/bsr20181523
|View full text |Cite
|
Sign up to set email alerts
|

MiR-384 induces apoptosis and autophagy of non-small cell lung cancer cells through the negative regulation of Collagen α-1(X) chain gene

Abstract: The present study aims to investigate the mechanism of miR-384 in non-small cell lung cancer (NSCLC) cell apoptosis and autophagy by regulating Collagen α-1(X) chain (COL10A1). Bioinformatics methods were applied to evaluate potential miRNAs and genes that might correlate with NSCLC. Tumor tissues and adjacent tissues from 104 NSCLC patients were collected and human NSCLC A549 cell line was selected for subsequent experiments. A549 cells were treated with miR-384 mimic, miR-384 inhibitor, or knockdown of COL10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…COL10A1 is a specific marker of hypertrophic chondrocyte. When chondrocytes are proliferating, they express SOX9 and COL2A1, but during differentiation into hypertrophic chondrocytes, COL10A1 is expressed and instead (Guo et al, ). As a result, knock‐down miR‐182‐5p was supposed to promote chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…COL10A1 is a specific marker of hypertrophic chondrocyte. When chondrocytes are proliferating, they express SOX9 and COL2A1, but during differentiation into hypertrophic chondrocytes, COL10A1 is expressed and instead (Guo et al, ). As a result, knock‐down miR‐182‐5p was supposed to promote chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interfering collagen biosynthesis enzymes Collagen genes MiR-129-5p, MiR-29b, MiR-384 [275][276][277] Prolyl 4-hydroxylase Budesonide, catechol, N-oxalylglycine, coumalic acid, ethyl dihydroxybenzoic acid [278][279][280] Heat shock protein 90 1G6-D7, dipalmitoyl-radicicol, 17-DMAG, ganetespib [281][282][283][284] Heat shock protein 47 MiR-29, 1,3-dimethylol-5-FU, AK778, pirfenidone, terutroban [285,286] Matrix metalloproteinases Gallium complex GS2, isoflavonoids, bisphosphonates [287,288] Lysyl oxidases Beta-aminopropionitrile [289] Disturbing cancer cell signaling pathways Snail transcription factors Toosendanin, ponicidin, ferulic acid [290] Hypoxia-inducible factor Tamoxifen, 28-O-propynoylbetulin [291,292] STAT3 signaling pathway VS-4718, stattic, ruxolitinib, S3I-201 [293,294] TGF-β signaling pathway LY2157299 monohydrate, trabedersen, fresolimumab, galunisertib [295,296] NF-κB signaling pathway Honokiol, aspirin, ormeloxifene [297][298][299] AKT signaling pathway Quetiapine, pirfenidone [300] Notch signaling pathway Rovalpituzumab tesirine, taladegib, crenigacestat, MiR-148a [301] Hedgehog signaling pathway Itraconazole, sonidegib, vismodegib [302] RAS signaling pathway Perindopril, losartan [100,303] Tyrosine kinase receptor Bevacizumab, imatinib, ponatinib, dasatinib [304,305] Discoidin domain receptor WRG-28, 7rh, AZD0156 [306][307][308] G protein family receptor AT13148, KD025, Azaindole 1, chelerythrine…”
Section: Effects Of Inhibitors Targeted Sites Of Inhibitors Typical Imentioning
confidence: 99%
“…c‐Jun N‐terminal kinase (JNK), also known as a stress‐activated protein kinase (SAPK) of the MAPK family, is initially activated in response to a variety of stress signals. miR‐26 inhibited cell autophagy of NSCLC, through inhibiting TGF‐β expression in a JNK‐dependent manner, both in vitro and in vivo . Collagen α‐1(X) chain (COL10A1), which encodes the α chain of type X collagen, is confirmed to be a member of the collagen family.…”
Section: Introductionmentioning
confidence: 99%
“…miR-26 inhibited cell autophagy of NSCLC, through inhibiting TGF-β expression in a JNK-dependent manner, both in vitro and in vivo. 87 Collagen α-1(X) chain (COL10A1), which encodes the α chain of type X collagen, is confirmed to be a member of the collagen family. Outcomes in vivo and in vitro suggested that miR-384 downregulated COL10A1 by targeting it, subsequently inhibiting cell proliferation and promoting cell autophagy in NSCLC cells.…”
mentioning
confidence: 99%